Using the Visual Technology "Lullia Circles" to Develop Preschool Children's Speech Preparation for School Education - Tashmuhamedova Feruza Batirjanovna (Miasto Przyszłości, 2025)
This article provides information on the methods and effectiveness of using innovative technologies, in particular, the "Lullia Circles" technology, in the process of preparing preschool children for school education.